Training on the manufacture of fiberglass materials using the vacuum infusion method in Pannampu Village, Makassar - Faisal Mahmuddin; Surya Hariyanto; M. Rusydi Alwi; Syerly Klara; Balqis Shintarahayu; Baharuddin Baharuddin; Muhammad Iqbal Nikmatullah; Haryanti Rivai; Fadel Rezky Ramadhan (Universitas Pendidikan Indonesia, 2025)
Fiberglass material has become a primary choice in the boatbuilding industry due to its superior strength and resistance to corrosion. The lamination process and the vacuum infusion method are the primary techniques in the manufacture of fiberglass boat structures. The combination of these two methods ensures that the glass fibers are evenly distributed and neatly arranged, providing optimal strength and durability to the fiberglass boat. The purpose of community service related to the lamination process, vacuum infusion, and the use of fiberglass is to increase public understanding of this technology and provide training and resources to fishermen, workers, and local industries to utilize it effectively in boat building and other products. The method of this community service activity employs a participatory socialization approach, which involves conducting an initial survey to gauge participants' understanding of the community service theme, followed by the delivery of socialization materials. Following this, discussion sessions were conducted, and post-surveys were administered to assess the differences in their level of understanding before and after the provision of the material. By understanding the lamination and vacuum infusion methods, as well as the application of fiberglass, the fishing community in Pannampu can enhance their skills in producing high-quality local fiberglass boats. Abstrak Material fiberglass telah menjadi pilihan utama dalam industri pembuatan kapal karena keunggulan kekuatannya yang tinggi dan ketahanannya terhadap korosi. Proses laminasi dan metode vacuum infusion adalah teknik utama dalam pembuatan struktur kapal fiberglass. Kombinasi kedua metode ini memastikan bahwa serat kaca terdistribusi secara merata dan tersusun dengan rapi, memberikan kekuatan dan ketahanan yang optimal pada kapal fiberglass. Tujuan dari pengabdian kepada masyarakat terkait dengan proses laminasi, vacuum infusion, dan penggunaan fiberglass adalah untuk meningkatkan pemahaman masyarakat tentang teknologi ini serta memberikan pelatihan dan sumber daya kepada nelayan, para pekerja, dan industri lokal untuk memanfaatkannya secara efektif dalam pembuatan kapal dan produk lainnya. Metode kegiatan pengabdian adalah menggunakan pendekatan sosialisasi partisipatif dengan melakukan survei awal yang berkaitan dengan pemahaman peserta tentang tema pengabdian dilanjutkan dengan pemberian materi sosialisasi. Setelah itu, dilakukan sesi diskusi dan dilakukan pascasurvei untuk mengetahui perbedaan tingkat pemahaman mereka sebelum dan sesuai pemberian materi. Dengan memahami metode laminasi dan vacuum infusion serta penerapan fiberglass, masyarakat nelayan di Pannampu dapat meningkatkan keterampilan mereka dalam memproduksi kapal fiberglass lokal yang berkualitas tinggi. Kata kunci: bahan fiberglass; Pannampu Makassar; pelatihan nelayan; vacuum infusion